Red-pink pigmented Hymenobacter coccineus sp. nov., Hymenobacter lapidarius sp. nov. and Hymenobacter glacialis sp. nov., isolated from rocks in Antarctica - Sedláček, Ivo; Králová, Stanislava; Kýrová, Kamila; Mašlaňová, Ivana; Busse, Hans-Jürgen; Staňková, Eva; Vrbovská, Veronika; Němec, Miroslav; Barták, Miloš; Holochová, Pavla; Švec, Pavel; Pantůček, Roman (International journal of systematic and evolutionary microbiology, 2017)
Four rod-shaped and Gram-stain-negative bacterial strains, CCM 8647, CCM 8649T, CCM 8643T and CCM 8648T, were isolated from rock samples collected on James Ross Island, Antarctica. Extensive biotyping, fatty acid profiling, chemotaxonomy, 16S rRNA gene sequencing and whole-genome sequencing was applied to isolates to clarify their taxonomic position. Phylogenetic analysis based on 16S rRNA gene sequencing indicated that all four isolates belonged to the genus Hymenobacter. Strains CCM 8649T and CCM 8647 were most closely related to Hymenobacter arizonensis OR362-8T (94.4 % 16S rRNA gene sequence similarity), strain CCM 8643T to Hymenobacter terrae DG7AT (96.3 %) and strain CCM 8648T to Hymenobacter glaciei VUG-A130T (96.3 %). The predominant fatty acids of CCM 8649T and CCM 8647 were summed feature 3 (C16 : 1ω7c/C16 : 1ω6c), C16 : 1ω5c and iso-C15 : 0, whereas those of CCM 8643T and CCM 8648T were summed feature 3 (C16 : 1ω7c/C16 : 1ω6c) and C16 : 1ω5c. The quinone systems contained exclusively menaquinone MK-7. The major polyamine was sym-homospermidine. All four strains contained the major polar lipid phosphatidylethanolamine. The G+C content of genomic DNA ranged from 60-63 mol%. Whole-genome sequencing data supported the finding that isolates represented distinct species of the genus Hymenobacter. On the basis of the results obtained, three novel species are proposed for which the names Hymenobacter coccineus sp. nov., Hymenobacter lapidarius sp. nov. and Hymenobacter glacialis sp. nov. are suggested, with the type strains CCM 8649T (=LMG 29441T=P5239T), CCM 8643T (=LMG 29435T=P3150T) and CCM 8648T (=LMG 29440T=P5086T), respectively.
Keywords: zastoupení bazí; Spermidine; Cytophagaceae; vitamin K 2; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; Vitamin K 2; mastné kyseliny; fosfatidylethanolaminy; Phylogeny; Sequence Analysis, DNA; sekvenční analýza DNA; Antarktida; Fatty Acids; Antarctic Regions; Pigmentation; DNA, Bacterial; DNA bakterií; spermidin; Base Composition; Phosphatidylethanolamines; RNA ribozomální 16S; Bacterial Typing Techniques; pigmentace